How does leader humility influence team performance?: exploring the mechanisms of contagion and collective promotion focus - Owens, Bradley P.; Hekman, David R. (New York: Academy of Management, 2016)
Using data from 607 subjects organized into 161 teams (84 laboratory teams, 77 organizational field teams), we examined how leader humility influences team interaction patterns, emergent states, and team performance. We develop and test a theoretical model, positing that, when leaders behave humbly, followers emulate their humble behaviors, creating a shared interpersonal team process (collective humility). This, in turn, creates a team emergent state focused on progressively striving toward achieving the team$1 (Bs highest potential (collective promotion focus), which ultimately enhances team performance. We test our model across three studies wherein we manipulate leader humility to test the social contagion hypothesis (Study 1), examine the impact of humility on team processes and performance in a longitudinal team simulation (Study 2), and test the full model in a multistage field study in a health services context (Study 3). Our findings collectively support our theoretical model, demonstrating that leader behavior can spread via social contagion to followers, producing an emergent state that ultimately affects team performance. We contribute to the leadership literature by suggesting the need for leaders to lead by example and showing how a specific set of leader behaviors influence team performance, providing a template for future leadership research on a wide variety of leader behaviors.s
Keywords: Leadership style, Leadership personality , -- Personality trait -- Job performance -- United States